Analisis Minat Belajar Peserta Didik Kelas VII dengan Menggunakan LKPD Inkuiri Terstruktur Berbantuan Quick Response Code - Rifda Nur Hikmahwati Arif (JURNAL ILMIAH RESEARCH STUDENT, 2023)
This research aims to determine the learning interest of class VII students at SMPN 18 Makassar using structured inquiry LKPD assisted by quick response codes on ecology material. This type of research is descriptive research with a quantitative approach. The research method used is a survey method. The research population was all class VII students at SMPN 18 Makassar. The sampling technique used was purposive sampling and a sample of 17 class VII students at SMPN 18 Makassar was obtained. The research instrument uses a non-test instrument in the form of a questionnaire which has been validated by the validator. The data analysis technique uses descriptive statistics. The results of the research show that the learning interest of class VII students at SMPN 18 Makassar using structured inquiry LKPD assisted by a quick response code on ecological material is that by using the structured inquiry LKPD assisted by a Quick Response Code, the learning interest of class VII students at SMPN 18 Makassar is at an average value of the average is 64, which is in the medium category. Furthermore, the frequency of each category is that the interest in learning of the 17 students who were respondents, as many as 2 students (11%) had a very high tendency, and as many as 2 students (11%) had a high tendency, then interest in learning was in the medium category. with the highest frequency, namely 47% and 3 students (17%) had low interest in learning, 17% were in the low category and finally there were 2 students (11%) who had students' interest in learning in the very low category.